The essence of modern transborder processes and its categorical reflection - Ustych, Serhii (Ukrainian Sociological Journal, 2015)
In the article the factors that contribute to the increasing importance of modern transborder processes are analyzed. The basic problems of their sociological reflection: the lack of clarity in the definition of the main categories, substitution of notions, following the principle of political expediency are described. To solve these problems the author proposes to use the system methodology of the study of social phenomena. From the standpoint of system vision definition of the category «transborder processes» has been proposed; the essence of transborder phenomena and its level structure is explored. The importance of system understanding of the tribal categories for the analysis of modes, in particular, such as «transborder cooperation» and «transborder statistics» is considered. The efficiency of system methodology for solving practical issues in management of transborder processes is underlined and evidenced by the results of the international projects implemented by the Institute for transborder cooperation, particularly within the EU ENPI Program and the International Visegrad Fund.